From honors education to regular education: learning from the content of innovations - Pierre van Eijl; Albert Pilot; Ron Weerheijm (Journal of the European Honors Council, 2023)
At the introduction of honors programs in Dutch higher education, stakeholders assumed that honors education could stimulate innovation in regular education. Whether this assumption holds was researched in the ‘Transfer of honors education to regular education’ project. This article focuses on the question of whether teachers’ experiences with honors education stimulated innovations in regular education and about structural characteristics in relation to the content, teaching formats, and pedagogics of the innovations. Interviews were conducted with teachers from four universities of applied sciences in the Netherlands. The results show that teachers in regular education found honors programs to provide them an opportunity to work with content, teaching formats, and pedagogics that they were unfamiliar with. Through these teachers, the honors approach inspired innovation in regular programs. Strikingly, these innovations contain to some degree all 14 structural characteristics of honors education distinguished in this study. The findings indicate the great innovative potential of honors education for regular education.